Description of Harpagorhynchus golvaneuzeti n. gen. n. sp. (Acanthocephala, Harpagorhynchinae n. sub-fam.) with a review of acanthocephalan parasites of soleid fishes in the Mediterranean Basin - Kvach Yuriy; de Buron Isaure (Parasite, 2019)
A species of acanthocephalan new to science from soleid fishes in the Mediterranean Sea and the Sea of Marmara is described. The new species is characterised by individuals having a club-shaped proboscis armed with 12–13 rows of 6–7 rooted hooks of a single type, a basal cerebral ganglion, and tegumental spines on the anterior two thirds of the body. Males have six cement glands and females show spines around the genital opening. To accommodate this species, a new genus, Harpagorhynchus n. gen., and a new subfamily in Echinorhynchidae, Harpagorhynchinae n. sub-fam., are erected. A critical review of the literature on echinorhynchid species infecting soleid fishes in the Mediterranean basin showed that Solearhynchus soleae (Porta, 1906) should be considered a junior synonym of S. rhytidotes (Monticelli, 1905) and that S. kostylewi (Meyer, 1932) is a valid species. An identification key of acanthocephalans of Mediterranean soleids is provided.